Oral health and self-perceived job readiness among socially disadvantaged and unemployed citizens - Anna Munk Sigsgaard; Steffen Altmann; Katrine Dannemand Jensen; Børge Hede; Esben Boeskov Øzhayat (Medical Journals Sweden, 2024)
Objective: The aims of this article are (1) to evaluate the association between oral health-related quality of life (OHRQoL) and self-perceived job readiness and (2) to investigate changes in self-perceived job readiness following an oral health promotion intervention. Materials and methods: The first aim was elucidated in a cross-sectional design, and the second through a prospective intervention study. A survey was administered among 273 unemployed vulnerable people in Copenhagen, Denmark. Participants were randomised to either control or intervention in 2018, and follow-up was conducted 7-15 months later. The intervention entailed support for dental care. OHRQoL was measured by the Oral Health Impact Profile (OHIP-14), and self-perceived job readiness was measured using the Employability Indicator Project (BIP) questionnaire. Results: The sample reported a high mean OHIP-14 score at baseline (26.9, SD 15.6) and poor OHRQoL was significantly associated with low self-perceived job readiness (rs = -0.15, p = 0.02). The control group reported better job readiness at follow-up compared to the intervention group. However, the effect sizes were small in both groups and no clear pattern was observed. Conclusions: The results indicate that OHRQoL is linked to self-perceived job readiness. However, the oral health promotion applied in this study did not lead to better self-perceived job readiness. Further research is needed on the effect of oral health promotion interventions on job readiness within socially vulnerable groups.